One Health study of mobile colistin resistance (mcr) in Salmonella enterica in Canada, 2017–2022 - Ketna Mistry; David Thumbi; Xiao Rui Li; Audrey Charlebois; Brent P. Avery; Anne E. Deckert; Ashley C. Cormier; Colleen Murphy; Ashley Kearney; Jennifer Campbell; Sara Christianson; David C. Alexander; et al. (Microbiology Spectrum)
ABSTRACT Colistin is a last-resort treatment for highly drug-resistant bacterial infections. Of 47,184 Salmonella isolates collected from 2017 to 2022 in Canada from human and animal/food sources, mobile colistin resistance (mcr) variants conferring colistin resistance were detected exclusively in humans (n = 15). These variants were mcr-1.1 (n = 7), mcr-3.1 (n = 5), mcr-3.2 (n = 2), and mcr-1.2 (n = 1). The most common mcr-containing serotypes were I 4,[5],12:i:- (n = 8) and Typhimurium (n = 3). The proportion of Salmonella carrying mcr genes remains low in Canada (0.03%).IMPORTANCEColistin can be used in combination with other drugs as salvage therapy for extensively drug-resistant infections. If mobile colistin resistance (mcr) becomes widely disseminated in Enterobacterales, colistin will no longer be an option for salvage therapy in otherwise untreatable infections. While colistin is not commonly used to treat human Salmonella infections, Salmonella represents an important reservoir of mcr genes that may be transmitted to other gram-negative bacteria. Our aim was to determine the occurrence of mcr genes in Salmonella isolates collected from humans, food animals, and retail meats in Canada.